Potential of Bio-briquette of Pineapple Crown Waste (Ananas comosus (L.) merr - Kurnia Nur Addina; Lazulva Lazulva (Universitas Negeri Medan, 2019)
This study aims to determine the potential of pineapple crown waste to be used as natural fuel in the form of biobriquettes, The research method used in this study is an experimental method. The research carried out in several stages, namely collection of raw materials, dehydration of raw materials, carbonization, crushing and screening, mixing binder, molding and compressing, drying and briquettes quality determining. The research findings showed that the bio-briquette quality of pineapple crown was 5.2-2.2% based on water content test, kabout 200-150 minutes, heating a liter water wiyh 200 grams bio-briquette was 23-15 minutes. All results of bio-briquette quality test of pineapple crown passed the SNI 06-3730-1995.